A dual‐fluorescence reporter in the Eomes locus for live imaging and medium‐term lineage tracing. Issue 8 (14th July 2017) - Probst, Simone; Daza, Ray A.; Bader, Natalie; Hummel, Jonas F.; Weiß, Matthias; Tanriver, Yakup; Hevner, Robert F.; Arnold, Sebastian J.
Summary: The T‐box transcription factor Eomes (also known as Tbr2 ) shows short‐lived expression in various localized domains of the embryo, including epiblast cells during gastrulation and intermediate progenitor cells in the cerebral cortex. In these tissues Eomes fulfills crucial roles for lineage specification of progenitors. To directly observe Eomes ‐dependent cell lineages in the living embryo, we generated a novel dual‐fluorescence reporter allele that expresses a membrane‐bound tdTomato protein for investigation of cell morphology and a nuclear GFP for cell tracing. This allele recapitulates endogenous EOMES protein expression and is suitable for live imaging. We found that the allele can also be used as a short‐to‐medium‐term lineage tracer, as GFP persists in cells longer than EOMES protein and marks Eomes ‐dependent lineages with a timeframe of days to weeks depending on the proliferation rate. In summary, we present a novel genetic tool for investigation of Eomes ‐dependent cell types by live imaging and lineage tracing.